(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
The enhancement of speaking competence poses a significant challenge in English as a Second Language (ESL) classrooms. Visual methodologies, such as images, flashcards, infographics, digital media, and interactive visual prompts, offer substantial contexts that promote communication and stimulate active learner engagement. This thesis investigates the pedagogical significance of visual tools in improving oral proficiency, focusing on learner motivation, vocabulary activation, and the alleviation of speaking anxiety. By referencing recent research in applied linguistics and educational psychology, the study underscores how visuals foster a more interactive, student-centered environment conducive to authentic communicative practices. The findings indicate that visual support not only enhances comprehension but also cultivates confidence in spontaneous speech production, rendering it an essential strategy for ESL pedagogy in modern educational contexts.